Adhesive bacterial amyloid nanofiber-mediated growth of metal–organic frameworks on diverse polymeric substrates. Issue 25 (8th June 2018) - Zhang, Cuizheng; Li, Yingfeng; Wang, Hongliang; He, Sanfeng; Xu, Yiyi; Zhong, Chao; Li, Tao
Abstract : Adhesive curli nanofibers, bacterial biofilms' major protein component, were utilized to mediate the growth of MOFs on various polymeric substrates. Abstract : The development of a simple, robust, and generalizable approach for spatially controlled growth of metal–organic frameworks (MOFs) on diverse polymeric substrates is of profound technological significance but remains a major challenge. Here, we reported the use of adhesive bacterial amyloid nanofibers, also known as curli nanofibers (CNFs), major protein components of bacterial biofilms, as universal and chemically/mechanically robust coatings on various polymeric substrates to achieve controlled MOF growth with improved surface coverage up to 100-fold. Notably, owing to the intrinsic adhesive attributes of CNFs, our approach is applicable for MOF growth on both 2D surfaces and 3D objects regardless of their geometric complexity. Applying this technique to membrane fabrication afforded a thin-film composite membrane comprising a 760 ± 80 nm ZIF-8 selective layer grown on a microporous polyvinylidene fluoride (PVDF) support which exhibited a C3 H6 /C3 H8 mixed-gas separation factor up to 10, C3 H6 permeance up to 1110 GPU and operational stability up to 7 days. Our simple yet robust approach therefore provides new insights into designing new interfaces for mediating MOF growth and opens new opportunities for constructing new MOF-based membranes and devices.